Mechanics of viscoelastic materials and wave dispersion - Chevalier, Yvon.; Tuong, Jean Vinh. (London : Iste, 2010)
Dynamic tests have proven to be as efficient as static tests and are often easier to use at lower frequency. Over the last 50 years, the methods of investigating dynamic properties have resulted in significant advances. This book explores dynamic testing, the methods used, and the experiments performed, placing a particular emphasis on the context of bounded medium elastodynamics. The discussion is divided into four parts. Part A focuses on the complements of continuum mechanics. Part B concerns the various types of rod vibrations: extensional, bending, and torsional. Part C is devoted to mechanical and electronic instrumentation, and guidelines for which experimental set-up should be used are given. Part D concentrates on experiments and experimental interpretations of elastic or viscolelastic moduli. In addition, several chapters contain practical examples alongside theoretical discussion to facilitate the readers understanding. The results presented are the culmination of over 30 years of research by the authors and as such will be of great interest to anyone involved in this field.
Elements of anisotropic elasticity and complements on previsional calculations / Yvon Chevalier -- Elements of linear viscoelasticity / Yvon Chevalier -- Two useful topics in applied viscoelasticity: constitutive equations for viscoelastic materials / Yvon Chevalier and Jean Tuong Vinh -- Formulation of equations of motion and overview of their solutions by various methods / Jean Tuong Vinh -- Torsional vibration of rods / Yvon Chevalier, Michel Nugues and James Onobiono -- Bending vibration of a rod / Dominique Le Nizhery -- Longitudinal vibration of a rod / Yvon Chevalier and Maurice Touratier -- Very low frequency vibration of a rod by Le Rolland-Sorin's double pendulum / Mostefa Archi and Jean-Baptiste Casimir -- Vibrations of a ring and hollow cylinder / Jean Tuong Vinh -- Characterization of isotropic and anisotropic materials by progressive ultrasonic waves / Patrick Garceau -- Viscoelastic moduli of materials deduced from harmonic responses of beams / Tibi Beda [and others] -- Continuous element method utilized as a solution to inverse problems in elasticity and viscoelasticity / Jean-Baptiste Casimir.
Includes bibliographical references and index.
Print version record.
Keywords: Viscoelastic materials -- Mechanical properties -- Mathematical models; Flexible structures -- Vibration -- Mathematical models; Structural engineering -- Materials -- Mathematical models; Wave-motion, Theory of -- Mathematics; Dispersion -- Mathematical models; Wave equation; SCIENCE -- Nanoscience; Electronic books